DEVELOPING THE STAGES OF FORMATIVE ASSESSMENT COMPETENCE IN PRE-SERVICE TEACHERS (International Conference on Education, Psychology and Humanities, 2026)
The modernization of higher pedagogical education requires future teachers to possess advanced professional competencies, including the ability to apply formative assessment effectively in educational practice. Formative assessment is recognized as one of the most important approaches for improving teaching quality, supporting students' learning progress, and providing continuous feedback throughout the educational process.
Keywords: formative assessment, pre-service teachers, professional competence, assessment literacy, feedback, reflection, teacher education, competency-based approach.